EU Donors and health system strengthening: the love-hate relationship with the Global Fund. (17th December 2018) - Steurs, Lies; Orbie, Jan; Delputte, Sarah; Verschaeve, Joren
ABSTRACT: Since the 2000s, the proliferation of Global Health Initiatives such as the Global Fund have dramatically changed the field of global health. The European Union and several of its Member States have played an important role in the development of the Global Fund and have contributed considerable budgets to it. While the Fund has been successful in fighting priority diseases, it has also been criticized for impacting negatively on countries' health systems, which provoked a debate on health system strengthening (HSS) within the organization. Drawing on a literature review, aid statistics, interviews at headquarter and field level, and document analysis, this article researches the relation between EU donors and the Global Fund, with an explicit focus on the HSS debate. The findings indicate a 'love-hate relationship'. EU donors have loved the Global Fund's innovative institutional set-up and its 'saving lives' approach involving quick results. However, over the years they have become more critical about its narrow focus, advocating a shift towards more HSS. Whereas this has been partly successful at headquarters level, most notably the incorporation of concrete HSS commitments in the Global Fund's strategic documents, challenges at local level constrain their translation into funding and implementation measures.